3D bioprinted Head and Neck Squamous Cell Carcinoma (HNSCC) model using tunicate derived Nanocellulose (NC) bioink - Azhakesan, Alexya; Kern, Johann; Mishra, Ankit; Selhuber-Unkel, Christine; Affolter, Annette; Gatenholm, Paul; Rotter, Nicole; Bieback, Karen (Advanced healthcare materials, 2025)
Head and neck squamous cell carcinoma (HNSCC) are invasive solid tumors accounting for high mortality. To improve the clinical outcome, a better understanding of the tumor and its microenvironment (TME) is crucial. Three -dimensional (3D) bioprinting is emerging as a powerful tool for recreating the TME in vitro. To establish long-term HNSCC bioprinted constructs for personalized drug-testing, this proof-of-principle study aims to compare two different innovative tunicate-derived nanocellulose (NC) hydrogels against the widely used semi-synthetic gelatin methacryloyl (GelMA). Cell lines of different tumor origin sites are printed in TEMPO and Carboxy-NC, and GelMA in alginate (GelMAA). Both NC hydrogels show higher bioprintability than GelMAA. Carboxy-NC supported long-term HNSCC survival, proliferation, and maintenance of epithelial phenotype in 3D bioprinted constructs similar to GelMAA. The hydrogel microstructure revealed differences in pore size. Importantly, the established HNSCC bioprinted model allowed the testing of radiochemotherapy (RCT) both in cell lines and patient-derived cultures. Compared to a spheroid model, the cytotoxic effects are less, better reflecting the response in patients. The proof-of-principle findings indicate that Carboxy-NC is a viable alternative to gelatin-based bioink with improved bioprintability allowing personalized drug-testing. By adding other cell-types of the TME, this model can be advanced to a heterotypic one.